From Liberal Peace to Mutual Coexistence: China’s Approach to Global Conflict Resolution - Fitriandi, Adinda Salsabila; Fadhat, Faris Al (Universitas Sultan Ageng Tirtayasa, 2025)
China's emergence as a global power has sparked debates about its role in the structure of world peace. This research addresses the binary construction of China as either a challenger or supporter of liberal peace, focusing on the type and extent of its challenges. Using a qualitative methodology and case studies, this study provides insights into China's participation in the normative context of liberal peace and its efforts to transform existing peace components. The research explores China's alternative approach to peacebuilding, grounded in the Five Principles of Peaceful Coexistence, and its implications for the global order. Key findings highlight China's growing involvement in United Nations Peacekeeping Operations, its mediation efforts in conflicts like the Saudi Arabia-Iran dispute, and the use of economic cooperation as a peacebuilding tool, demonstrating a significant departure from the liberal peace paradigm.